Predictors of distress and poorer quality of life in High Grade Glioma patients - Halkett, Georgia; Lobb, E.; Rogers, M.; Shaw, T.; Long, A.; Wheeler, H.; Nowak, A. (Elsevier Ireland Ltd., 2015)
Objective: To determine High Grade Glioma (HGG) patients’ levels of distress and QOL during combined chemoradiotherapy, explore predictors of distress and QOL and prioritize patients’ supportive care needs. Methods: Patients diagnosed with HGG who were referred for combined chemoradiotherapy were recruited. Participants completed demographics and questionnaires assessing distress, function, and supportive care needs. Descriptive statistics, correlation coefficients, t-tests and linear and logistic regression analyses were performed. Results: 116 participants completed the questionnaire. Participants scored lower for QOL in physical, functional and emotional domains than the general Australian population. Poor physical function, lower education levels, loss of employment and financial impact associated with diagnosis were consistently linked with multiple domains of distress, poor QOL and high unmet needs. Having a carer who was their partner predicted lower emotional well-being. Conclusion: Patients with HGG experience a poor QOL, increased levels of distress and high unmet needs when commencing chemoradiotherapy. Patients who experience a financial impact and those with lower education levels may report higher levels of distress and increased unmet needs. Practice implications: Poor function, lower education and limited financial resources may help identify those who require additional screening and may benefit from additional information and psychological support at this time.